Comprehensive Review of Alternative Proteins in Pet Food: Research Publications, Patents, and Product Trends in Plant, Aquatic, Insect, and Cell-Based Sources - Phatthranit Klinmalai; Pitiya Kamonpatana; Arisara Thongpech; Janenutch Sodsai; Khwanchat Promhuad; Atcharawan Srisa; Yeyen Laorenza; Attawit Kovitvadhi; Sathita Areerat; Anusorn Seubsai; Shyam S. Sablani; Nathdanai Harnkarnsujarit (Foods)
The increasing demand for sustainable pet-food solutions has driven interest in alternative protein sources, as researchers seek to avoid allergenic foods while maintaining optimal pet nutrition. This review explores recent scientific publications, patent trends, and market trends relating to various alternative protein sources, including plant-based, aquatic, insect-derived, and cell-based sources. Their nutritional composition, functional properties, and potential benefits for pet health were assessed. Plant-based proteins, such as soy, pea, and lentils, provide essential amino acids and functional properties suitable for meat analogues. Microalgae and seaweed offer rich sources of omega-3 fatty acids, antioxidants, and bioactive compounds. Insect-based proteins such as black-soldier-fly larvae and mealworms are highly digestible and rich in essential nutrients, with additional benefits for gut health. Emerging cell-based proteins present a novel, lab-grown alternative with promising sustainability and nutritional advantages. While these protein sources offer significant benefits, challenges related to digestibility, palatability, regulatory approval, and consumer acceptance must be addressed. The emphasis of the present research is on current developments for industry uses and future potential. The analysis sheds light on the contributions of alternative protein sources to the promotion of sustainable and nutrient meals for pets.